2007
DOI: 10.1002/per.625
|View full text |Cite
|
Sign up to set email alerts
|

The moderator role of intuitive versus deliberative decision making for the predictive validity of implicit and explicit measures

Abstract: The Preference for Intuition and Deliberation (PID) scale aims at capturing stable general individual differences in terms of intuitive versus deliberative preferences in decision making. A study examined the psychometric properties of the English version of the PID, investigated whether the two subscales moderate the validity of implicit and explicit measures for incidental and deliberative evaluations and behaviours concerning fizzy soft drinks, and compared the predictive validity of two new implicit measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…These particular results support the notion that momentary changes in the level of internal and external cues have a significant impact on eating decisions. Of note, the influence of these cues on a person’s eating decisions potentially takes place implicitly without his or her conscious knowledge (4547)…”
Section: Discussionmentioning
confidence: 99%
“…These particular results support the notion that momentary changes in the level of internal and external cues have a significant impact on eating decisions. Of note, the influence of these cues on a person’s eating decisions potentially takes place implicitly without his or her conscious knowledge (4547)…”
Section: Discussionmentioning
confidence: 99%
“…Friese, Hofmann, & Wänke, in press;Hofmann, Rauch, & Gawronski, 2007;Penke, Eichstaedt, & Asendorpf, 2006;Richetin, Perugini, Adjali, & Hurling, 2007). For instance, Karpinski and Steinman (2006) applied a conceptually similar procedure, termed the Single-Category-IAT (SC-IAT).…”
Section: The Single-target Iat and Its Advantagesmentioning
confidence: 98%
“…There is accumulating evidence that these measures can, for instance, predict the amount of snacks or beverages consumed in a laboratory taste test (Friese et al, in press;Hofmann & Friese, in press;Richetin et al, 2007) or determine the evaluation of phobic stimuli (Huijding & de Jong, 2006). The value of a single-target measure is particularly evident when arbitrary counter-categories-such as the category 'other' in self-esteem and self-concept IATs-lessen criterion correlations (Karpinski & Steinman, 2006).…”
Section: Comparison To Other Single-category Measuresmentioning
confidence: 98%
“…Notwithstanding these considerations, research addressing people’s awareness of their implicit attitudes has primarily focused on correlations between implicit and explicit attitudes, and specifically on the factors that impact the magnitude of these correlations (Gschwendner at al., 2006; Jordan, Whitfield, & Zeigler-Hill, 2007; Ranganath, Smith, & Nosek, 2008; Richetin, Perugini, Perugini, Adjali, Hurling, 2007; Smith & Nosek, 2011). For example, Jordan et al (2007) found greater correspondence between implicit and explicit measures of self-esteem for people who scored higher on faith in intuition (i.e., chronically viewing their intuitions as more valid).…”
Section: Previous Researchmentioning
confidence: 99%